Patient–Provider Communication and Counseling about Gestational Weight Gain and Physical Activity: A Qualitative Study of the Perceptions and Experiences of Latinas Pregnant with their First Child - Ana Cristina Lindsay (International Journal of Environmental Research and Public Health, 2017)
Latina women in the United States (U.S.) are disproportionately affected by obesity and are more likely to begin pregnancy overweight and gain excessive weight during pregnancy. The prenatal care period represents a window of opportunity for women to access the healthcare system and receive preventive services, education, nutritional support, and other social services to improve pregnancy outcomes. Excessive gestational weight gain (GWG) has numerous negative short- and long-term consequences for both the mother and newborn. We explored nulliparous Latina women’s perceptions about their experiences communicating with their primary healthcare provider about GWG and physical activity (PA) to identify possible intervention targets using in-depth, semi-structured interviews. Bilingual, trained research staff conducted 23 interviews with first-time pregnant Latinas between 22 and 36 weeks of gestation. Interviews were transcribed verbatim and analyzed using content analysis. Salient text passages were extracted, shortened, coded, and grouped into categories. Women, including those who self-identified as being overweight or obese prior to pregnancy, reported receiving limited or no advice from their healthcare providers about GWG or PA. Additionally, analysis revealed that although participants value information received from the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) program counselors, they would like to receive more information from their primary healthcare providers about adequate GWG. Furthermore, study findings indicate that some participants received conflicting information regarding PA during pregnancy. Study findings suggest the need for increased integration of communication and counseling about GWG and PA into prenatal care services to promote healthy weight gain and PA among low-income Latina women.